Asymptomatic Glomus Tumor of the Mediastinum - Meletios Kanakis; Nikoletta Rapti; Maria Chorti; Achilleas Lioulias (Case Reports in Surgery)
Glomus tumors are rare benign neoplasms that predominate in limbs. Infrequently, they can occur in a wide anatomic distribution, to include sites not known to contain glomus cells. Although glomus tumors are usually small, pain and tenderness are common clinical symptoms. We report the case of a 69-year-old man with an asymptomatic large mediastinal glomus tumor, who underwent surgical resection.